PUBLIC SECTOR REFORMS IN NIGERIA: A STUDY OF THE TREASURY SINGLE ACCOUNT (Journal of the Management Sciences, 2025)
This study examines public sector reforms in Nigeria, focusing on the implementation of the Treasury Single Account (TSA) as a tool to enhance financial transparency and accountability. The background to the study stems from Nigeria's long-standing issues of corruption and inefficiency in public financial management. The objectives of the study are to assess the impact of TSA on improving government revenue control, reducing financial leakages, and enhancing budgetary discipline. The research methodology is conceptual, relying on secondary data to analyse the successes and challenges of the TSA policy. The findings revealed that TSA has significantly contributed to centralising government revenues, reducing opportunities for corruption, and improving cash management. However, challenges such as initial resistance from government agencies, technological gaps, and capacity-building needs hindered full implementation. The study concludes that while TSA has strengthened financial oversight, addressing its operational challenges is key to maximising its effectiveness. Recommendations include strengthening technological infrastructure, enhancing public sector staff capacity, and fostering stakeholder collaboration to ensure long-term success. This analysis highlights the critical role of financial management reforms in promoting transparency and accountability in Nigeria’s public sector.
Keywords: Governance; Public Sector; Reforms; TSA; Nigeria